The Strategy of The Sustainable Livelihoods for Beef Farmers in Bima Regency After the Flood Disaster in April 2021 - Kharismafullah, Kharismafullah; Azizah, Siti; Budiarto, Agus (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
The purpose of this study is to know the sustainable livelihood strategies of beef cattle farmers in Bima region after the flood disaster by using the concept of Sustainability Livelihood Framework (SLF). The research method used in this study is descriptive qualitative. The sampling method is purposive sampling and snowball sampling. Primary data collection methods are observation and interviews while the secondary data collection method is by accessing the Department of Animal Husbandry and Animal Health in Bima region and Bank Negara Indonesia (BNI). The result of this livelihoods strategy research for the beef cattle farmers is to respond the vulnerability by participating in forest reforestation. The government awareness to enforce the rules, moving the livestock on corn farm locations, moving livestock in locations provided by village government and in Lar Doroncanga, utilizing social media and social networks to anticipate communal conflicts. Using the services of a veterinarian to treat livestock diseases, process livestock waste into compost and biogas, sell livestock in abattoirs, use social media and social networks to sell livestock seeds, using the services of Artificial Insemination officers (IB). Utilizing of savings and capital assistance from banks to buy livestock seeds, utilizing of the livestock insurance programs to anticipate vulnerabilities and buying livestock breeds in Sumbawa District and East Nusa Tenggara (NTT).